Synthesis and characterization of a Sr0.95Y0.05TiO3−δ-based hydrogen electrode for reversible solid oxide cells. Issue 22 (11th March 2015) - Ling, Yihan; Chen, Luyang; Lin, Bin; Yu, Weili; Isimjan, Tayirjan T.; Zhao, Ling; Liu, Xingqin
<x xml:space="preserve">Abstract</x> Reversible solid oxide cells (RSOCs) can generate electricity as solid oxide fuel cells (SOFC) facing a shortage of electricity and can also store the electricity as solid oxide electrolysis cells (SOEC) at the time of excessive electricity.